Literature Survey: The Potential of Integrating Immersive Experience and Aesthetic Experience in Virtual Reality Historical Event - Mohd Ekram Al Hafis Hashim, Muhammad Zaffwan Idris (Tanjung Malim, 2024)
Literature Survey: The Potential of Integrating Immersive Experience and Aesthetic Experience in Virtual Reality Historical Event by Mohd Ekram Al Hafis Hashim, Muhammad Zaffwan Idris